2021
DOI: 10.1002/bmc.5266
|View full text |Cite
|
Sign up to set email alerts
|

Total saponins from stems and leaves of Panax quinquefolius L. ameliorate podophyllotoxin‐induced myelosuppression and gastrointestinal toxicity

Abstract: Podophyllotoxin (POD), a natural lignan distributed in podophyllum species, possesses significant antitumor and antiviral activities. But POD often causes serious side effects, such as myelosuppression, gastrointestinal toxicity, neurotoxicity, hepatic and renal dysfunction, and even death, which not only hinder its clinical application but also threaten the patient's health. Therefore, an effective treatment against POD-induced toxicity is important. Our preliminary study found that the total saponins from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Among them, ginsenoside is considered the main active ingredient for its efficacy and can be divided into three categories according to the position and number of glycol groups on its aglycones, the majority of which are dammarane and oleanolic acid (Chang et al, 2016;Chen & Cui, 2002;Choi, 2008;Sun et al, 2018;Zhang et al, 2022;Zhang et al, 2021). among different metabolites; therefore, the mechanism of drugs can be further revealed (Chen et al, 2015;Sun et al, 2018;Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, ginsenoside is considered the main active ingredient for its efficacy and can be divided into three categories according to the position and number of glycol groups on its aglycones, the majority of which are dammarane and oleanolic acid (Chang et al, 2016;Chen & Cui, 2002;Choi, 2008;Sun et al, 2018;Zhang et al, 2022;Zhang et al, 2021). among different metabolites; therefore, the mechanism of drugs can be further revealed (Chen et al, 2015;Sun et al, 2018;Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, more than 300 active components have been isolated, such as ginsenosides, polysaccharides, volatile oils, organic acids, alkaloids, amino acids, trace elements, and vitamins (Wang et al, 2018; Wang et al, 2021). Among them, ginsenoside is considered the main active ingredient for its efficacy and can be divided into three categories according to the position and number of glycol groups on its aglycones, the majority of which are dammarane and oleanolic acid (Chang et al, 2016; Chen & Cui, 2002; Choi, 2008; Sun et al, 2018; Zhang et al, 2022; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased levels of the EPA in breast adipose tissue may increase the risk of breast cancer in ammation which will leading to poor prognosis[48].Oxoglutarate is associated with multiple metabolic pathways, including arginine synthesis, butyrate metabolism, citric acid cycle, and alanine, aspartate, and glutamate metabolism. Studies have shown that arginine metabolism disorders are associated with myelosuppression induced by podophyllotoxin[49]. Oxoglutarate can be generated by the oxidative decarboxylation of isocitrate, and animal model have shown that the citrate intermediate succinate can increase hemoglobin, platelet and neutrophil levels and improve chemotherapy-induced myelosuppression[50].…”
mentioning
confidence: 99%